Molecular identification of root-lesion nematodes, Pratylenchus spp. in agricultural crops from Costa Rica - Sandoval-Ruiz, Rebeca (2022)
Introduction. The root-lesion nematodes, Pratylenchus spp., have a wide host range and reduce the yield of different crops. Information on the diversity of Pratylenchus species is scarce in Costa Rica. Objective. To identify the Pratylenchus species associated with 12 crops based on the D3 region of the 28S rDNA gene. Materials and methods. During 2013 to 2015, root samples were collected in Alajuela, Cartago, Guanacaste, Heredia, and San José in crops of rice (Oryza sativa), black pepper (Piper nigrum), sugarcane (Saccharum officinarum), aster (Aster sp.), coffee (Coffea arabica), banana (Musa paradisiaca), lily (Lilium sp.), gypsophila (Gypsophila sp.), onion (Allium cepa), potato (Solanum tuberosum), strawberry (Fragaria x ananassa), and leather-leaf fern (Rumohra adiantiformis). The D3 region of the 28S rDNA gene from each population was amplified and sequenced. A GenBank Blast Search was performed for each sequence. The phylogenetic relationships were established by Bayesian Inference. Results. Blast Search indicated the presence of P. pseudocoffeae in aster, P. brachyurus in black pepper, P. crenatus in onion and potato, P. hippeastri and P. gutierrezi in sugarcane and coffee, respectively. Pratylenchus bolivianus in leather-leaf fern and potato, P. penetrans in onion, strawberry, gypsophila, and lily, P. zeae in rice and sugarcane, while P. speijeri in banana. The phylogenetic analysis corroborated the Pratylenchus species identity with exceptions of sequences from 1) banana, grouped to P. coffeae complex group, 2) sugar cane, grouped to P. hippeastri complex group 3) onion and potato were related with P. crenatus, in an independent group, and 4) leather-leaf fern and potato were grouped with P. bolivianus with low resolution. Conclusions. Nine genetic groups of Pratylenchus were found, some of those should be verified with other molecular markers to get a conclusive identification.